Essentials of Modern Optical Fiber Communication - Noé, Reinhold (Springer Berlin Heidelberg : Imprint: Springer, 2016)
This is a concise introduction into optical fiber communication. It covers important aspects from the physics of optical wave propagation and amplification to the essentials of modulation formats and receivers. The combination of a solid coverage of necessary fundamental theory with an in-depth discussion of recent relevant research results enables the reader to design modern optical fiber communication systems. The book serves both graduate students and professionals. It includes many worked examples with solutions for lecturers. For the second edition, Reinhold Noé made many changes and additions throughout the text so that this concise book presents the essentials of optical fiber communication in an easy readable and understandable way.